การเห็นคุณค่าในตนเองและพฤติกรรมการใช้เฟสบุ๊คของคน Generation Y ในกรุงเทพมหานคร - กชพร ธัญญานุรักษา (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Nowadays, one of the most influential things in our life is Social Media especially Facebook and the top user of Facebook in Thailand is Generation Y. Although Facebook is very useful and convenience but in the other hand it can cause many negative effects and one of them is low self-esteem. However, Self-esteem and Facebook usage behavior in Generation Y has not been studied much in Thailand. This research aimed to study about self-esteem and Facebook usage behavior and to determine self-esteem and its relationship with Facebook usage behavior among generation Y in BangkokThis research is a cross-sectional descriptive study. The subjects were 285 participants, 22-38 years old in Bangkok, randomly selected. The research instruments consisted of questionnaires regarding demographic information, Facebook usage behavior information, Bergen Facebook Addiction Scale (Thai-BFAS) and Rosenberg Self-Esteem Scale (Revised Thai RSES). The results were presented in frequency and percentage for the demographic information, Facebook usage behavior information, Facebook Addiction Scale and Self-Esteem Scale in generation Y in Bangkok and other factors related to self-esteem will be analyzed by chi-squared test, correlation and linear regression analysis.Among this 285 subjects, there were high level of self-esteem (32.3%) and low level of self-esteem (11.6%), respectively. 17.5% of subjects were addicted to Facebook. The statistically significance associated factors with self-esteem were age, education, income, objective for using Facebook (trend), time spent on Facebook, frequency to post or comment on Facebook and Facebook addiction which is also associated to self-esteem in a negative relationship.Consequently, low self-esteem in generation Y was associated with Facebook usage behavior. Therefore, reducing low level of self-esteem should beware and protect people from risk factors and be considered for the mental health campaign to balance self-esteem.